A Call for Responsibility: Social Media and the Need to Monitor Hate Speech and Fake News for Global Peace - Darban, karim; Kabbaj, Smail (Ali Institute or Research and Publication, 2023)
This paper explores the pivotal role of social media in fostering peace and examines responsible monitoring practices to counteract hate speech and fake news propagation. Leveraging an interdisciplinary approach, our research method entailed case studies and a systematic review of existing literature encompassing studies on social media's impact on public opinion, the spread of misinformation, and successful instances of peace promotion through online platforms. Our findings indicate that while social media has the potential to facilitate peacebuilding, the challenges posed by hate speech and misinformation persist. We elucidate the crucial role of artificial intelligence (AI) and human moderation in identifying and mitigating harmful content, underscoring the need for transparent algorithms, human oversight, and continual evaluation. This paper also highlights successful case studies where social media has been instrumental in bridging divides and promoting dialogue. We contend that by addressing these challenges and implementing responsible monitoring strategies, social media should contribute to a more peaceful and inclusive online environment.